Optimising Qur’anic Reading Ability through the Jibril Method: A Qualitative Case Study in Indonesian Madrasah Tsanawiyah - Amyadi; Ahmad Khumaidi; Nuramin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Qur’anic reading instruction in Indonesian Islamic junior secondary schools (madrasah tsanawiyah) frequently confronts persistent learner heterogeneity in makhraj (articulation), tajwid (recitation rules), and reading fluency, with predominantly teacher-centred methods failing to accommodate individual learning needs. This study examined the implementation of the Jibril Method and its contribution to Qur’anic reading skill development at MTs Nurur Rahmah Sambirampak Lor Kotaanyar, Probolinggo, Indonesia. A qualitative single case study design was employed with 20 purposively sampled informants: two Qur’anic teachers, twelve Grade VII-VIII students with at least one semester of programme participation representing high, moderate, and low reading ability, one school principal, and five parents. Data were generated through eight structured classroom observations, twenty in-depth semi-structured interviews, and systematic document analysis. The Miles, Huberman, Saldaña interactive thematic model was applied, with trustworthiness established through source, technique, and time triangulation and member checking. Findings reveal that the Jibril Method is implemented through four integrated pedagogical components: (1) talqin (teacher modelling of correct recitation), (2) taqlid (student imitation as observational learning), (3) repetitive practice (3–5 repetitions per identified error), and (4) immediate corrective feedback. Across five indicators makhraj accuracy, tajwid application, reading fluency, reading confidence, and learner engagement documented evidence confirmed gradual, progressive improvements over the eight-session observation period, corroborated by teacher records, student accounts, and parent reports. The study offers an empirically grounded four-component pedagogical model that positions the Jibril Method as a theoretically coherent approach integrating Social Learning Theory, skill automaticity, and formative assessment principles, with practical implications for adaptive Qur’anic literacy instruction in formal Islamic school contexts.